Artificial Intelligence in Higher Education : A Literature Snapshot - Ms. Janhvee Vivek Boratkar; Dr. Rajeshkumar U. Sambhe (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In Artificial Intelligence, “Artificial” means objects that are produced by human beings, and “Intel ligence” is the capability to form tactics to achieve goals by interacting with huge information. Artificial Intelligence (AI) is evolving rapidly in higher education, and various AI applications have been developed to solve some of the most pressing problems that higher education field currently face. The use of Artificial Intelligence or AI is rising in higher education. With this rise, the morality of AI programs is being questioned Higher education is crucial for producing ethical citizens and profess ionals globally. The introduction of generative AI (GenAI), such as ChatGPT, has posed opportunities and challenges to the traditional model of education. However, the current conversations primarily focus on policy development and assessment, with limited research on the future of higher education.AI - powered language tools (AILTs) are commonly used by university students, yet there is a limited understanding of how students utilize and perceive these tools in everyday academic communication practice. Following the very recent launch of the ChatGPT, chatbot, numerous comments and speculations were posted concerning the potential aspects of society that are expected to benefit from this AI revolution. This paper addresses some of the most fundamental questions about the role, position, and implications of ChatGPT and generative artificial intelligence (AI) tools amidst the evolving landscape of higher education and modern society.AI education aims to teach AI concepts, essential knowledge, and skills related to the fundamental ideas in AI. The affordances of artificial intelligence (AI) have not been totally utilized in education. To effectively integrate AI into education, teachers’ AI - specific technological and pedagogical knowledge is important.
Keywords: Artificial Intelligence; Higher Education; Chat GPT; Personalized learning; Engineering Education